2
Объяснение:
x² – 2|x| – 48 = 0
1) при x<0 |x|=-x
x² + 2x – 48 = 0
D=2²+4*48=4+4*48=4(1+48)=4*49=2²*7²
√D=2*7=14
x₁=(-2-14)/2=-8
x₂=(-2+14)/2=6 не подходит, так как не удовлетворяе требованию x<0
2)при x≥0 |x|=x
x² - 2x – 48 = 0
√D=14
x₁=(2-14)/2=-6 не подходит, так как не удовлетворяе требованию x≥0
x₂=(2+14)/2=8
2 решения
2
Объяснение:
x² – 2|x| – 48 = 0
1) при x<0 |x|=-x
x² + 2x – 48 = 0
D=2²+4*48=4+4*48=4(1+48)=4*49=2²*7²
√D=2*7=14
x₁=(-2-14)/2=-8
x₂=(-2+14)/2=6 не подходит, так как не удовлетворяе требованию x<0
2)при x≥0 |x|=x
x² - 2x – 48 = 0
√D=14
x₁=(2-14)/2=-6 не подходит, так как не удовлетворяе требованию x≥0
x₂=(2+14)/2=8
2 решения